ALKBH5 acts a tumor-suppressive biomarker and is associated with immunotherapy response in hepatocellular carcinoma - Hehua Ma; Yuxin Hong; Zhenzhen Xu; Zuyi Weng; Yuanxun Yang; Dandan Jin; Zhiyou Chen; Xuan Zhou; Zhi Xu; Fei Fei; Wei Song; Juan Li (Scientific Reports)
Abstract As immune-checkpoint inhibitors (ICIs) therapy has made great strides in hepatocellular carcinoma (HCC) treatment, improving patient response to this strategy has become the main focus of research. Accumulating evidence has shown that m6A methylation plays a crucial role in the tumorigenesis and progression of HCC, while the precise impact of the m6A demethylase ALKBH5 on the tumor immune microenvironment (TIME) of HCC remains poorly defined. The clinical significance of ALKBH5 and TIM3 were evaluated in human HCC tissues. The biological function of ALKBH5 was analyzed in vitro and in vivo. The HCC molecular subtypes were identified based on key ALKBH5-regulated methylation-related genes (MRGs). The differences in survival, clinical features, TIME and immunotherapy response between these two subtypes were then evaluated. The regulation of ALKBH5 on TIM3 was detected by qPCR, western blotting and MeRIP. ALKBH5 was downregulated in HCC and associated with worse prognosis. ALKBH5 inhibited the proliferation and migration activities of HCC cells in vitro and in vivo. The HCC subtype with high expression of key MRGs was characterized by immunosuppression phenotypes and a worse response to ICIs. Moreover, TIM3 was identified as a target of ALKBH5. Upregulated TIM3 level was negatively correlated with survival in HCC. The results of this study suggest that ALKBH5 is an important regulator in HCC progression. ALKBH5 exerts its influence on the TIME and immunotherapy response by targeting TIM3 in HCC. This work provides new insight into the correlation between m6A modification and ICI response, which may help provide therapeutic benefits to HCC patients.